Service Quality Management in Passport Issuance at Class I TPI Immigration Office Surabaya - Laksmi, I Gusti Ayu Dini Riarti Laretna; Mustofa, Amirul; Widyawati, Widyawati (Socious Journal, 2024)
This study aims to evaluate the quality management of services in the passport issuance process at the Class I Immigration Office TPI Surabaya. High-quality and efficient services are essential to meet the public’s needs for travel documents, particularly passports. However, despite being regulated by strict standards, service implementation occasionally encounters obstacles that may impact applicants' experiences. This research focuses on how service management quality at the Surabaya Immigration Office affects applicant satisfaction and effectiveness in achieving the expected service standards. The method used in this study is qualitative. Data were obtained through in-depth interviews with immigration officers and direct observation of the service process in the field. The study results indicate that the management of passport issuance services at the Class I Immigration Office TPI Surabaya is quite effective, with various indicators showing high achievements. Service process effectiveness reached 85%, while service speed was at 90%, demonstrating good service standards despite occasional technical issues. Resource use efficiency was recorded at 88%, reflecting the optimization of technology to reduce manual workload. Officer responsiveness scored 92%, while the quality of interaction between officers and applicants reached 93%, indicating friendly and professional service that enhances public satisfaction. Based on these findings, it is concluded that, overall, the Class I Immigration Office TPI Surabaya has successfully met public expectations in passport issuance services. Recommendations include increasing service capacity through technology optimization, expanding officer training, and educating applicants about required documents and digital systems to improve future service effectiveness